1996
DOI: 10.1128/jb.178.1.61-67.1996
|View full text |Cite
|
Sign up to set email alerts
|

The gntP gene of Escherichia coli involved in gluconate uptake

Abstract: The gntP gene, located between the fim and uxu loci in Escherichia coli K-12, has been cloned and characterized. Nucleotide sequencing of a region encompassing the gntP gene revealed an open reading frame of 447 codons with significant homology to the Bacillus subtilis gluconate permease. Northern (RNA) blotting indicated that the gntP gene was monocistronic and was transcribed as an mRNA with an apparent molecular size of 1.54 kb. The transcriptional start point was determined by primer extension analysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 29 publications
0
46
0
Order By: Relevance
“…Sequence analysis indicated a CRP binding site in the gntP regulatory region. This location, at position Ϫ42 with respect to the previously mapped transcription start site (10), is indicative of class II activation (3). A gntP-lacZ operon fusion was repressed 7-and 3.5-fold in the presence of glucose or gluconate, respectively, by comparison to LB medium alone (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sequence analysis indicated a CRP binding site in the gntP regulatory region. This location, at position Ϫ42 with respect to the previously mapped transcription start site (10), is indicative of class II activation (3). A gntP-lacZ operon fusion was repressed 7-and 3.5-fold in the presence of glucose or gluconate, respectively, by comparison to LB medium alone (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we are interested in gntP, which was implicated as being important for colonization of the mouse intestine by a human commensal E. coli strain (30). gntP is one of four genes which encode gluconate transporters (20), but previous studies showed that it is not induced by gluconate (10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The GntlI was demonstrated to be repressed by the presence of pyruvate [3,8]. Recently, a thermoresistant gluconokinase was purified from E. coli and characterized [10], and another permease encoded by the gntP gene with the high affinity for gluconate was uncovered in E. coli [11].…”
Section: Introductionmentioning
confidence: 99%